1437Rates of low value care in NSW public hospitals: variation between public and private inpatients. (2nd September 2021) - Costa, Juliana de Oliveira; Pearson, Sallie-Anne; Elshaug, Adam; Gool, Kees van; Jorm, Louisa; Falster, Michael
Abstract: Background: Low value care (LVC) services have limited or no benefit to patients, and curtailing LVC can curb unnecessary spending and improve the quality of care. Some public hospitals in Australia have financial incentives to perform procedures for patients with private health insurance, yet little is known if there are differences in LVC between public and private patients. Methods: We performed a retrospective analysis of New South Wales public hospital data from January 2013 to June 2018. We measured hospital-specific rates of five LVC services and compared rates within each public hospital by patient funding status (private or public), descriptively and using random-slope multilevel models. Results: Overall rates of LVC varied between services, ranging from 0.3 to 30.8 procedures per 1, 000 eligible patients for hyperbaric oxygen therapy and vertebroplasty, respectively. There was large variation in rates of the LVC services between hospitals, and a few hospitals had higher rates of LVC among private than public patients. However, we found no consistent association between patient funding status and LVC services: private patients had lower rates of knee arthroscopic debridement than public patients (aOR:0.56) and higher rates of low value vertebroplasty for osteoporotic spinal fractures (aOR:1.08), hyperbaric oxygen therapy (aOR:1.53) and oophorectomy (aOR:1.77); all statistically non-significant. Conclusions: Private patient funding may contribute to LVC in some public hospitals, but it was not consistently associated with higher rates of the five LVC services measured. Key messages: Reducing LVC services requires investigating the role of health-system factors at both the global- and local-level.